Effect of Air Fuel Ratio on Engine Performance of Single Cylinder Port Injection Hydrogen Fueled Engine: A Numerical Study - M. M., Rahman; R. A., Bakar (2009)

(untitled)
This paper focuses on the effect of air-fuel ratio on the engine performance of single cylinder hydrogen fueled port injection internal combustion engine. GT-Power was utilized to develop the model for port injection engine. One dimensional gas dynamics was represented the flow and heat transfer in the components of the engine model. The governing equations are introduced first, followed by the performance parameters and model description. Air-fuel ratio was varied from stoichiometric limit to a lean limit. The rotational speed of the engine was varied from 2500 to 4500 rpm while the injector location was considered fixed in the midway of the intake port. The acquired results show that the air-fuel ratio is greatly influence on the performance of hydrogen fueled engine. It is shown that the brake mean effective pressure (BMEP) and brake thermal efficiency decreases with increases of the air-fuel ratio however the brake specific fuel consumption (BSFC) increases with increases of the air-fuel ratio. The cylinder temperature decreases with the increase of air-fuel ratio. The present model emphasizes the ability of retrofitting the traditional engines with hydrogen fuel with minor modifications.